Photophysical properties of some poly(siloxane–azomethine)s. (August 2015) - Tigoianu, Ionut Radu; Airinei, Anton; Ribitsch, Volker; Gruber, Christian; Fifere, Nicusor; Vlad, Angelica; Cazacu, Maria
The responsive optical properties of some poly(siloxane–azomethine)s incorporating 1, 8-dihydroxyanthraquinone units (PSA1 and PSA2) toward various metal ions (nickel (Ni 2+ ), copper (Cu 2+ ), silver, zinc, ferric, manganese, calcium (Ca 2+ ), chromium, cadmium, barium, magnesium, lead, mercury, strontium, and cobalt) were investigated by steady-state and time-resolved fluorescence techniques. The fluorescence quenching has shown a significant deviation from the Stern–Volmer linearity due to the effect of combination of dynamic and static quenching for PSA1 in the presence of metal ions. Generally, the fluorescence decay is described by a two-exponential relation. The fluorescence of these PSAs was efficiently quenched by Cu 2+ and Ni 2+ ions, and these derivatives could be investigated as a promising system for the development of new sensors for the detection of Cu 2+ .